2018
DOI: 10.3389/fmicb.2018.01635
|View full text |Cite
|
Sign up to set email alerts
|

New Biological Insights Into How Deforestation in Amazonia Affects Soil Microbial Communities Using Metagenomics and Metagenome-Assembled Genomes

Abstract: Deforestation in the Brazilian Amazon occurs at an alarming rate, which has broad effects on global greenhouse gas emissions, carbon storage, and biogeochemical cycles. In this study, soil metagenomes and metagenome-assembled genomes (MAGs) were analyzed for alterations to microbial community composition, functional groups, and putative physiology as it related to land-use change and tropical soil. A total of 28 MAGs were assembled encompassing 10 phyla, including both dominant and rare biosphere lineages. Ama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 83 publications
2
58
0
4
Order By: Relevance
“…Ecosystem functioning depends to a large extent on the functional diversity and activity of the belowground microbial system [5,6]. In addition, microorganisms play a key role in decomposing soil organic matter and mineralizing nutrients in soil [7]. It has been shown that rainforest conversion to plantations has negative effects on the biodiversity of fungi [8,9], protists [10], vertebrates [11], insects and plants [12][13][14], archaea [15], but not on bacterial diversity which increased [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Ecosystem functioning depends to a large extent on the functional diversity and activity of the belowground microbial system [5,6]. In addition, microorganisms play a key role in decomposing soil organic matter and mineralizing nutrients in soil [7]. It has been shown that rainforest conversion to plantations has negative effects on the biodiversity of fungi [8,9], protists [10], vertebrates [11], insects and plants [12][13][14], archaea [15], but not on bacterial diversity which increased [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The comparative data in Fig 6 cluster genes by the sequences of the 16S rRNA gene identified in this study. This analysis was carried out as a survey of biotechnological potential [18,19] mainly related to biodegradation in the storage tanks of water contaminated with agrochemicals, which are considered a significant environmental liability.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the composition and relative abundance of soil microbiomes in the Amazon were correlated with different types of land use, such as deforestation, which leads to carbon cycle disturbances and, consequently, climate change [18]. Therefore, microbiomes, which play key roles in biogeochemical cycles, are affected by anthropogenic action, particularly by the use of xenobiotic compounds, leading to changes in sustainability and environmental quality [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, belowground biodiversity loss is very likely to have negative effects both on the environment and on the sustainability of agricultural production as microbial functions will be altered (Tardy et al, 2014). Recently, metagenomic approaches have investigated the impact on the composition and structure of soil microbiome of converting semi-deciduous Amazonian rainforest and natural grasslands to arable soils (Mendes et al, 2015;Castañeda and Barbosa, 2017;Goss-Souza et al, 2017;Kroeger et al, 2018). These studies found that arable soils were similar or more diverse than the original ecosystem and that functional redundancy overcomes the ecosystem transformation.…”
Section: Discussionmentioning
confidence: 99%